2017
DOI: 10.1111/tpj.13488
|View full text |Cite
|
Sign up to set email alerts
|

Impact of light intensity and quality on chromatophore and nuclear gene expression in Paulinella chromatophora, an amoeba with nascent photosynthetic organelles

Abstract: SUMMARYPlastid evolution has been attributed to a single primary endosymbiotic event that occurred about 1.6 billion years ago (BYA) in which a cyanobacterium was engulfed and retained by a eukaryotic cell, although early steps in plastid integration are poorly understood. The photosynthetic amoeba Paulinella chromatophora represents a unique model for the study of plastid evolution because it contains cyanobacterium-derived photosynthetic organelles termed 'chromatophores' that originated relatively recently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 72 publications
0
42
0
Order By: Relevance
“…Notably, among the short LC import candidates were the nuclear-encoded PSI subunits PsaE and PsaK, which have been demonstrated before to be part of PSI [13]. Other short import candidates were four EGT-derived high-light-inducible (HLI) photoprotective proteins [10,11] and two proteins annotated as cold-shock proteins. However, most of the short import candidates do not have homologs in other organisms (67 proteins) or are conserved proteins of unknown function (10 proteins).…”
Section: Chromatophore-encoded Proteinsmentioning
confidence: 97%
See 1 more Smart Citation
“…Notably, among the short LC import candidates were the nuclear-encoded PSI subunits PsaE and PsaK, which have been demonstrated before to be part of PSI [13]. Other short import candidates were four EGT-derived high-light-inducible (HLI) photoprotective proteins [10,11] and two proteins annotated as cold-shock proteins. However, most of the short import candidates do not have homologs in other organisms (67 proteins) or are conserved proteins of unknown function (10 proteins).…”
Section: Chromatophore-encoded Proteinsmentioning
confidence: 97%
“…The chromatophore is surrounded by two envelope membranes and a peptidoglycan layer [7]. Its genome (1 Mb) is reduced to approximately one-third of the ancestral cyanobacterial genome [8], and >70 genes of a-cyanobacterial origin, which most likely result from endosymbiotic gene transfers (EGTs) from the chromatophore, are now expressed from the nuclear genome [9][10][11]. Overall, nuclear-and chromatophore-encoded functions are highly complementary, with many genes for proteins involved in the same metabolic pathway or cellular process being distributed over both chromatophore and nuclear genome [9].…”
Section: Introductionmentioning
confidence: 99%
“…The chromatophore genome is highly reduced, encoding 867 proteins that represent about one-third of proteins of its free-living counterparts (Nowack et al, 2008). Similar to the EGTs found in Archaeplastida, P. chromatophora has relocated > 70 chromatophore genes into the nuclear genome (mostly involved in photosynthesis-related functions) (Nowack et al, 2016;Zhang et al, 2017). By contrast, these genes represent < 1% of the Paulinella nuclear genome, while in A. thaliana some reports have suggested that the genes of cyanobacterial origin can account for up to 18% of the nuclear genes (Martin et al, 2002).…”
Section: New Phytologist Similarities Between Primary Endosymbioses Imentioning
confidence: 99%
“…A bacteria-reduced culture was used for HiSeq 2500 and Illumina Nova Seq 6000 sequencing. For transcriptome sequencing, control and high light stress conditions (control=10 µmol photons m -2 sec -1 ; stress=120 µmol photons m -2 sec -1 ; see Zhang, et al 2017) over a 12/ 12h light/ dark cycle and temperature stress conditions (control=24°C; stress=4°C, 38°C) were sequenced using the Illumina Truseq stranded mRNA library prep kit. All sequencing was done by DNA Link Inc. (Seoul, Korea).…”
Section: Sequencing and Genome Size Estimationmentioning
confidence: 99%
“…In contrast to the highly reduced plastid genomes of algae and plants (i.e., 100-200 kbp in size in Archaeplastida), the cyanobacterium-derived plastid (referred to as the chromatophore) in phototrophic Paulinella is in a less derived stage of organelle evolution and is ca. 1 Mbp in size (Lhee, et al 2017;Nowack, et al 2008;Reyes-Prieto, et al 2010;Zhang, et al 2017).…”
Section: Introductionmentioning
confidence: 99%